Is Geographical Isolation Associated with Poorer Outcomes for Northern Manitoba First Nation Communities? - Lavoie, Josée G.; Phillips-Beck, Wanda; Avery Kinew, Kathi; Sinclair, Stephanie; Kyoon-Achan, Grace; Katz, Alan (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2021)
This study tested the assumption that geographical isolation is associated with poorer population health outcomes among First Nations in Manitoba. Our results show higher premature mortality rates (PMR) in northern communities, declining slower than for any other Manitoba communities. Our results also show lower ambulatory care sensitive conditions (ACSC) hospitalization rate in the North, suggesting barriers to prevention and early diagnosis. There remains a large gap in ACSC hospitalization rates between First Nations and all Manitobans. Further research is warranted to understand the relationship between the changes in the rates of ACSC and the difference in the rates between northern and southern communities.